Surviving Persia: Esther's Scroll, Anti-Black Racism and the Propaganda of Peace and Progress - De-Whyte, Janice P. (Religions, 2022)
Esther, Mordecai and the Jewish People’s survival in ancient Persia alert readers that anti-Semitism can exist even in professedly peaceful and progressive settings. Esther’s scroll is not only designed to be read, but it too reads contemporary circumstances of trauma and oppression. This Hebrew Bible narrative offers a critique and a challenge to present interpreters, especially those belonging to professed progressive and peaceful societies. Esther’s scroll exposes how the propaganda of peace and progress, foundational to various imperial and institutional contexts, can veneer structures and events of violence and trauma. Informed by the death-dealing realities of anti-Black racism, a reading of Esther’s key scenes and themes provides insight into the destructive and deadly ways that injustices such as anti-Black racism are supported and sustained by institutional policies and practices. Inherent within this Jewish survival account is an indictment of complicit and culpable individuals and institutions that enable, fund and sanction violence against marginalized members. Although there are numerous sites of oppression and violence throughout society, this essay highlights the institution of academia, which is often upheld as a paragon of progress and peace but which is frequently a prime site of racism and its attendant inequities. As a piece of trauma and survival literature, Esther’s scroll makes a valuable contribution to the repertoire of resilience and resistance curated by many Black individuals and communities to counter anti-Black racism.